2017
DOI: 10.5194/bg-14-5675-2017
|View full text |Cite
|
Sign up to set email alerts
|

Climate engineering and the ocean: effects on biogeochemistry and primary production

Abstract: Abstract. Here we use an Earth system model with interactive biogeochemistry to project future ocean biogeochemistry impacts from the large-scale deployment of three different radiation management (RM) climate engineering (also known as geoengineering) methods: stratospheric aerosol injection (SAI), marine sky brightening (MSB), and cirrus cloud thinning (CCT). We apply RM such that the change in radiative forcing in the RCP8.5 emission scenario is reduced to the change in radiative forcing in the RCP4.5 scena… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 38 publications
1
30
1
Order By: Relevance
“…However, recent studies such as Eliseev (2012) or Keith et al (2017) suggest that SRM might be understood as a form of carbon dioxide removal (CDR) technique because of its impacts on the global carbon cycle. This statement is also supported by former studies (Eliseev, 2012;Govindasamy et al, 2002;Keller et al, 2014;Lauvset et al, 2017;Matthews & Caldeira, 2007;Muri et al, 2015;Sonntag et al, 2018) which suggest that SRM is likely to strengthen carbon uptake by both ocean and terrestrial ecosystems. This finding is also supported by the modeled response of the carbon cycle to major volcanic eruptions (Brovkin et al, 2010;MacMartin et al, 2016;Rothenberg et al, 2012;Tjiputra & Otterå, 2011).…”
Section: Introductionsupporting
confidence: 75%
“…However, recent studies such as Eliseev (2012) or Keith et al (2017) suggest that SRM might be understood as a form of carbon dioxide removal (CDR) technique because of its impacts on the global carbon cycle. This statement is also supported by former studies (Eliseev, 2012;Govindasamy et al, 2002;Keller et al, 2014;Lauvset et al, 2017;Matthews & Caldeira, 2007;Muri et al, 2015;Sonntag et al, 2018) which suggest that SRM is likely to strengthen carbon uptake by both ocean and terrestrial ecosystems. This finding is also supported by the modeled response of the carbon cycle to major volcanic eruptions (Brovkin et al, 2010;MacMartin et al, 2016;Rothenberg et al, 2012;Tjiputra & Otterå, 2011).…”
Section: Introductionsupporting
confidence: 75%
“…Recent studies investigating the impacts of SAI on global and regional climate (e.g., Berdahl et al, 2014;Kravitz et al, 2015;Muri et al, 2018) suggest that the overall effect of SAI is the amelioration of global-scale warming by reducing the incoming shortwave radiation. Therefore, there are large impacts on land and ocean carbon cycling on a global scale (Lauvset et al, 2017;Muri et al, 2018;Tjiputra et al, 2016). Our previous study using SAI method showed that global mean surface temperature can be reduced by 2°C by the year 2100 and 5°C by the year 2200 compared to its baseline RCP8.5 scenario (Tjiputra et al, 2016).…”
Section: 1029/2018ef001146mentioning
confidence: 99%
“…However, unequal responses of drylands to individual RFG methodologies are substantial over CNA, WSH, and AUS. The cooling over the ocean surface by the MSB leads to bimodal patterns between tropical and subtropical North Pacific (Lauvset et al, 2017). When CCT is implemented, thinner cirrus clouds increase incoming solar radiation and strengthens radiative cooling in the upper troposphere.…”
Section: Discussionmentioning
confidence: 99%
“…Also, the warming in lower troposphere and cooling in upper troposphere promote convections and enhance the global hydrological cycle (Kristjánsson et al, 2015). The cooling over the ocean surface by the MSB leads to bimodal patterns between tropical and subtropical North Pacific (Lauvset et al, 2017). These changes enhance convective activities over the western Pacific and eastern Indian Ocean, which alters the Pacific Walker circulation similarly to that under a La Ninã event (Niemeier et al, 2013;Stjern et al, 2018).…”
Section: Discussionmentioning
confidence: 99%